2012
DOI: 10.3109/14653249.2012.729817
|View full text |Cite
|
Sign up to set email alerts
|

Is CD34 truly a negative marker for mesenchymal stromal cells?

Abstract: The prevailing school of thought contents that mesenchymal stem cells (MSCs) do not express CD34, and this sets MSCs apart from hematopoietic stem cells (HSCs), which express CD34. However, the evidence for MSCs being CD34- is largely based on cultured MSCs, not tissue-resident MSCs, and the existence of CD34- HSCs is in fact well documented. Furthermore, the Stro-1 antibody, which has been extensively used for the identification/isolation of MSCs, was generated by using CD34+ bone marrow cells as immunogen. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
151
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(164 citation statements)
references
References 51 publications
13
151
0
Order By: Relevance
“…These MSLCs comprised both CD34-positive and -negative cells, despite being CD45-negative. [20]. In this study, we confirmed that calcification of CD34-negative MSLCs was rapidly induced using high inorganic phosphate (3.2 mM).…”
Section: Discussionsupporting
confidence: 79%
“…These MSLCs comprised both CD34-positive and -negative cells, despite being CD45-negative. [20]. In this study, we confirmed that calcification of CD34-negative MSLCs was rapidly induced using high inorganic phosphate (3.2 mM).…”
Section: Discussionsupporting
confidence: 79%
“…Lin et al suggest that available evidence points to CD34 being expressed in tissue-resident MSC and its negative finding being a consequence of cell culturing. In addition, CD34 expression in vivo 31: 1139-1144 (2017) correlates with enhanced vasculogenic and angiogenic potential, but also with replicative capacity and stemness, while loss of CD34 expression might be related to lineage commitment (15). In our study, we evaluated the CD34 expression using two antibodies, one for chicken/human CD34 (cCD34) and another one for human CD34 (hCD34).…”
Section: Discussionmentioning
confidence: 99%
“…CD34, a hematopoetic stem cell marker, has also been identified in bone marrowmesenchymal stem cells and adipose tissue-derived stem cells (20). Importantly, the frequency of this progenitor population showed selective expansion in liver injury associated with Mdr2 deficiency.…”
Section: Fig 6 Gp38mentioning
confidence: 98%